Temporal aspects of affective states, physiological responses, and perceived exertion in competitive cycling time trials - Davis, P. A.; Stenling, A. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Athletes` affective states can vary dramatically before, during, and after competition. Further, intense affect is associated with physiological responses that may amplify biological reactions manifested from the execution of physical tasks underlying performance. Fluctuations in perceptual cues (eg, perceived exertion) and physiological responses (eg, blood lactate, heart rate) can influence performance and vary dramatically in relation to competition. However, the pattern of these fluctuations and potential associations between perceptual cues and biological responses may also diverge during task execution with differential implications for performance. Data collected from highly trained athletes (N = 25; Mage = 25.4) during a competition (ie, maximum total distance) comprised of three 7-minute cycling time trials and were analyzed with longitudinal multilevel modeling. Results showed that affective states were negatively associated with perceived exertion at the within-person level and negatively associated with heart rate at the between-person level within each trial. Blood lactate and heart rate were positively associated at the between-person level, whereas heart rate was positively associated with perceived exertion at the within-person level. The anticipation of more pleasurable affective states predicted less decline in affective states, but not physiological responses, during each trial. Anticipated affective states prior to each trial were also associated with affective states upon its completion. These findings suggest associations among perceptual cues and physiological responses may differ depending on the level of analysis (between- vs. within-person level associations), and anticipated affective states prior to performance may influence affective states during and after task execution.